Substituent effects in the decarboxylation reactions of coordinated arylcarboxylates in dinuclear copper complexes, [(napy)Cu2(O2CC6H4X)]+†. Issue 6 (December 2017) - Jin, Qiuyan; Li, Jiaye; Ariafard, Alireza; Canty, Allan J; O'Hair, Richard AJ
A combination of gas-phase ion trap mass spectrometry experiments and density functional theory (DFT) calculations have been used to examine the role of substituents on the decarboxylation of 25 different coordinated aromatic carboxylates in binuclear complexes, [(napy)Cu2 (O2 CC6 H4 X)] +, where napy is the ligand 1, 8-naphthyridine (molecular formula, C8 H6 N2 ) and X = H and the ortho ( o ), meta ( m ) and para ( p ) isomers of F, Br, CN, NO2, CF3, OAc, Me and MeO. Two competing unimolecular reaction pathways were found: decarboxylation to give the organometallic cation [(napy)Cu2 (C6 H4 X)] + or loss of the neutral copper benzoate to yield [(napy)Cu] + . The substituents on the aryl group influence the branching ratios of these product channels, but decarboxylation is always the dominant pathway. Density functional theory calculations reveal that decarboxylation proceeds via two transition states. The first enables a change in the coordination mode of the coordinated benzoate in [(napy)Cu2 (O2 CC6 H4 X)] + from the thermodynamically favoured O, O -bridged form to the O -bound form, which is the reactive conformation for the second transition state which involves extrusion of CO2 with concomitant formation of the CO2 coordinated organometallic cation, [(napy)Cu2 (C6 H4 X)(CO2 )] +, which then loses CO2 in the final step to yield [(napy)Cu2 (C6 H4 X)] + . In all cases the barrier is highest for the second transition state. The o -substituted benzoates show a lower activation energy than the m -substituted ones, while the p -substituted ones have the highest energy, which is consistent with the experimentally determined normalised collision energy required to induce fragmentation of [(napy)Cu2 (O2 CC6 H4 X)] + .